Runx2 Transcriptional Activation of Indian Hedgehog and a Downstream Bone Metastatic Pathway in Breast Cancer Cells - Pratap, Jitesh (2008)
Runx2, required for bone formation, is ectopically expressed in breast cancer cells. To address the mechanism by which Runx2 contributes to the osteolytic disease induced by MDA-MB-231 cells, we investigated the effect of Runx2 on key components of the “vicious cycle” of TGFβ mediated tumor growth and osteolysis. We find that Runx2 directly upregulates Indian Hedgehog (IHH) and colocalizes with Gli2, a Hedgehog signaling molecule. These events further activate parathyroid hormone related peptide (PTHrP). Furthermore, Runx2 directly regulates the TGFβ induced PTHrP levels. A subnuclear targeting deficient mutant Runx2 which disrupts TGFβ induced Runx2-Smad interactions, failed to induce IHH and downstream events. In addition, Runx2 knockdown in MDA-MB-231 inhibited IHH and PTHrP expression in the presence of TGFβ. In vivo blockade of the Runx2-IHH pathway in MDA-MB-231 cells by Runx2 shRNA inhibition prevented the osteolytic disease. Thus, our studies define a novel role of Runx2 in upregulating the vicious cycle of metastatic bone disease, in addition to Runx2 regulation of genes related to progression of tumor metastasis.